Integrasi Ekoteologi dan Maqashid Syariah dalam Tata Kelola Zakat Hijau: Analisis Green Zakat Framework Indonesia - A Afif Amrullah; Roibin; M Lutfi Mustofa (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
The global climate crisis requires multi-stakeholder collaboration and resource allocation, including optimizing zakat for environmental sustainability. The aim of this research is to analyze the Green Zakat Framework released by Badan Amil Zakat Nasional (BAZNAS), Bank Syariah Indonesia (BSI), the United Nations Development Programme (UNDP), and IPB University. This research is a literature review using a descriptive-analytical approach. The results demonstrate that the integration of ecotheology and maqasid sharia serves as a legitimate basis for developing green zakat governance in Indonesia, which is not only viewed as a socio-economic obligation but also has an environmental sustainability dimension. Its implementation is translated into four pillars of zakat governance: collection, management, distribution, and reporting, oriented towards hifz al-bi'ah (environmental protection) and the achievement of the sustainable development goals (SDGs).